Obesity and Pro12Ala Polymorphism of Peroxisome Proliferator-Activated Receptor-Gamma Gene in Healthy Adults: A Systematic Review and Meta-Analysis - Anahita Mansoori; Maryam Amini‎; Fariba Kolahdooz; Ensiyeh Seyedrezazadeh (2015)
Background: The aim of this systematic review was to evaluate the relationship between obesity and peroxisome proliferator-activated receptor-gamma (PPARγ) Pro12Ala polymorphism in healthy adults. Summary: Weighted mean differences (WMDs) of body mass index (BMI) were calculated for different inheritance models and subgroups. Fifty-six studies were eligible for inclusion in the meta-analysis. The result shows that the Ala allele of this polymorphism was associated with increased WMD in mean BMI (WMD = 0.29, 95% CI 0.10-0.48, p = 0.003). The Ala carriers were associated with increased WMD in mean BMI values in both genders and in the Caucasian subgroup. The associations were seen among people with higher levels of BMI (BMI ≥35). Message: The Ala allele of the PPARγ Pro12Ala polymorphism in healthy adults was associated with increased BMI under a dominant model of inheritance.